Comparative evaluation of fresh and freeze-dried 3D-printed wound dressings with Plantago major extract: In vitro primerjava svežih in liofiliziranih 3D natisnjenih materialov za oskrbo ran z vgrajenim ekstraktom P. major - Činč Ćurić, Laura; Maver, Uroš; Maver, Tina (Acta Medico-Biotechnica, 2025)
Aim: In this study, we prepared an extract of Plantago major L. (PM) herb and assessed its safety and impact on fibroblast metabolic activity (MA) across a broad concentration range. Additionally, we examined the effects of dry and fresh three dimensionally (3D)-printed wound dressings (abbreviated: dressing) on fibroblasts and evaluated their influence on cell migration and proliferation by a scratch assay.Methods: We prepared a methanolic PM extract and investigated its effect on fibroblast MA across various concentrations. Using 3D printing, we fabricated dressings composed of methylcellulose, alginate, and nanofibrillated cellulose, incorporating the extract. Subsequently, we assessed the effects of dry and fresh dressings on fibroblast MA as well as on migration/proliferation by a scratch assay.Results: T he e xtract h ad n o c ytotoxic e ffects a t c oncentrations of 1–1,000 μg/mL, but became cytotoxic at 10,000 μg/mL. Fibroblast MA increased up to a concentration of 1,000 μg/mL, after which it began to decline, indicating a hormetic effect. The dry dressing enhanced fibroblast MA 1.2-fold more than the control (normalized to 1.0) and the fresh dressing (0.99-fold). The scratch assay confirmed that both dressings supported fibroblast migration/proliferation equally.Conclusions: Our in vitro results support the traditional use of PM in wound healing and can serve as a basis for future investigation of this plant in clinical trials.
Keywords: P. major; 3D printing; skin fibroblasts; wound healing